Performance Analysis of XOR-Based Routing Protocols in Vehicular ad hoc Networks - Dinis, Rui (2011)
This book is part of a series exploring the dynamic universe of the Internet in the 21st century. Collected here are papers discussing a wide range of topics and issues impacting and relating to the Internet such as: internet traffic conditioning methods applied to wireless networks; design knowledge management and sharing using XML; FGPA-Based video streaming; internet traffic modeling and an analysis of XOR-based flat routing protocols. (Imprint: Nova Press)